Hpv vaccination knowledge and awareness among male university students in Malaysia: a cross-sectional study - Li, Siqi; Ahmad Fauzi, Fatimah; Jin, Zhihai; Abdul Manaf, Rosliza (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background/Objectives: Human papillomavirus (HPV) vaccines are effective in preventing HPV infection and HPV-related cancers in both males and females. As sexual behavior plays a central role in HPV transmission, male vaccination is important not only for reducing HPV-associated diseases among men but also for limiting viral transmission at the population level. Methods: A cross-sectional study was conducted among male university students in Selangor, Malaysia. Data were collected using a structured questionnaire assessing sociodemographic characteristics, history of sexual intercourse, HPV-related knowledge, and awareness of HPV vaccination. Multivariable logistic regression analysis was performed to identify factors associated with HPV vaccination awareness. Results: Overall, 43.4% of the respondents demonstrated good awareness of HPV vaccination. Multivariable logistic regression analysis identified several factors significantly associated with awareness. Non-Muslim students were more likely to report good awareness of HPV vaccination than Muslim students (AOR = 2.724, 95% CI: 1.150–6.454, p < 0.001). Students who were in a relationship or married demonstrated higher awareness compared with single students (AOR = 3.830, 95% CI: 2.071–7.082, p < 0.001). HPV-related knowledge showed the strongest association, with participants possessing good knowledge being more likely to be aware of HPV vaccination (AOR = 7.012, 95% CI: 4.077–12.059, p < 0.001). In contrast, history of sexual intercourse was not significantly associated with HPV vaccination awareness after adjustment (p = 0.097). Conclusions: Awareness of HPV vaccination among male university students was influenced by religion, relationship status, and HPV-related knowledge. These findings highlight the need for targeted, male-inclusive vaccination education strategies that address sociodemographic differences. University-based interventions may play an important role in improving awareness and increasing HPV vaccine uptake in this population.